2010
DOI: 10.1007/s11033-010-0660-7
|View full text |Cite
|
Sign up to set email alerts
|

CTLA-4 exon 1 +49 polymorphism alone and in a haplotype with −318 promoter polymorphism may confer susceptibility to chronic HBV infection in Chinese Han patients

Abstract: Cytotoxic T-lymphocyte-associated antigen 4 (CTLA-4) plays a pivotal role in regulating T cell activation, which is believably critical for the outcome of hepatitis B virus (HBV) infection. The expression and function of CTLA-4 may be affected by gene polymorphisms. This study investigated the influence of CTLA-4 polymorphisms on disease susceptibility in Chinese Han patients with chronic HBV infection. CTLA-4 +49A/G and -318C/T polymorphisms were evaluated by DNA amplification with polymerase chain reaction f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
39
0

Year Published

2011
2011
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(42 citation statements)
references
References 41 publications
3
39
0
Order By: Relevance
“…[16][17][18][19] However, few reports are available about the relation between CTLA-4 polymorphisms and susceptibility to viral infection after HSCT. In our previous studies, a significant association was found between CTLA-4 -1661 A/G and -318 C/T genotypes and CMV and hepatitis B virus infection, respectively, after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…[16][17][18][19] However, few reports are available about the relation between CTLA-4 polymorphisms and susceptibility to viral infection after HSCT. In our previous studies, a significant association was found between CTLA-4 -1661 A/G and -318 C/T genotypes and CMV and hepatitis B virus infection, respectively, after HSCT.…”
Section: Discussionmentioning
confidence: 99%
“…All the participants were of Chinese Han nationality and genetically unrelated. Of the 244 patients with chronic HBV infection, 120 patients were diagnosed with chronic hepatitis, 65 patients were diagnosed with liver cirrhosis, and 59 patients were diagnosed with HCC as had been described previously (Bruix and Sherman, 2005;Sorrell et al, 2009;Duan et al, 2011). The 76 subjects were classified as HBV infection resolvers based on the spontaneous recovery from HBV infection with serum negativity for HBsAg, HBeAg, and anti-HBe and positivity for anti-HBs and anti-HBc IgG.…”
Section: Study Subjectsmentioning
confidence: 99%
“…The AA genotype and A allele of the CTLA-4 49A/G, and the genotype CC of the CTLA-4 -318 C/T polymorphisms was seen more frequently in chronic HBV-infected patients. 2 Thio Abbreviations: CI, confidence interval; OR, odds ratio; SNP, single-nucleotide polymorphism *Considered significant with P value of .05. In genotypes, each P value is the result of comparing the corresponding row with the sum of the other rows.…”
Section: Discussionmentioning
confidence: 99%
“…Inefficiency of the host immune responses has been associated with the chronic and complicated HBV infection. 1,2 Immunologic genetic factors have played a role in altering the immune response and particularly, the outcome of HBV infection. 1,3 Therefore, understanding single nucleotide polymorphisms (SNPs) of several immunoregulatory genes (ie, costimulatory molecules) may be crucial for developing effective strategies against HBV.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation